LMS tables for waist circumference and waist-height ratio in Colombian adults: Analysis of nationwide data 2010 (2016)
Background/Objectives:Indices predictive of central obesity include waist circumference (WC) and waist-to-height ratio (WHtR). These data are lacking for Colombian adults. This study aims at establishing smoothed centile charts and LMS tables for WC and WHtR; appropriate cutoffs were selected using receiver-operating characteristic analysis based on data from the representative sample.Subjects/Methods:We used data from the cross-sectional, national representative nutrition survey (ENSIN, 2010). A total of 83 220 participants (aged 20-64) were enroled. Weight, height, body mass index (BMI), WC and WHtR were measured and percentiles calculated using the LMS method (L (curve Box-Cox), M (curve median), and S (curve coefficient of variation)). Receiver operating characteristics curve analyses were used to evaluate the optimal cutoff point of WC and WHtR for overweight and obesity based on WHO definitions.Results:Reference values for WC and WHtR are presented. Mean WC and WHtR increased with age for both genders. We found a strong positive correlation between WC and BMI (r=0.847, P less than 0.01) and WHtR and BMI (r=0.878, P less than 0.01). In obese men, the cutoff point value is 96.6 cm for the WC. In women, the cutoff point value is 91.0 cm for the WC. Receiver operating characteristic curve for WHtR was also obtained and the cutoff point value of 0.579 in men, and in women the cutoff point value was 0.587. A high sensitivity and specificity were obtained.Conclusions:This study presents first reference values of WC and WHtR for Colombians aged 20-64. Through LMS tables for adults, we hope to provide quantitative tools to study obesity and its complications.